Transplantation of CD3/CD19 depleted allografts from haploidentical family donors in paediatric leukaemia - Lang, Peter; Teltschik, Heiko-Manuel; Feuchtinger, Tobias; Müller, Ingo; Pfeiffer, Matthias; Schumm, Michael; Ebinger, Martin; Schwarze, Carl P.; Gruhn, Bernd; Schrauder, Andre; Albert, Michael H.; Greil, Johann; et al. (British journal of haematology, 2014)
Transplantation of T- and B-cell depleted allografts from haploidentical family donors was evaluated within a prospective phase II trial in children with acute lymphoblastic leukaemia, acute myeloid leukaemia and advanced myelodysplastic syndrome (n = 46). 20 patients had active disease; 19 patients received a second or third stem cell transplantation (SCT). Toxicity-reduced conditioning regimens consisted of fludarabine or clofarabine (in active disease only), thiotepa, melphalan and serotherapy. Graft manipulation was carried out with immunomagnetic microbeads. Primary engraftment occurred in 88%, with a median time to reach >1·0 × 109/l leucocytes, >20 × 109/l platelets and >0·1 × 109/l T-cells of 10, 11 and 50 days, respectively. After retransplantation, engraftment occurred in 100%. Acute graft-versus-host disease (GvHD) grade II and III-IV occurred in 20% and 7%, chronic GvHD occurred in 21%. Both conditioning regimens had comparable toxicity. Transplant-related mortality (TRM) was 8% at one year and 20% at 5 years. Event-free survival at 3 years was: 25% (whole group), 46% (first, second or third complete remission [CR], first SCT) vs. 8% (active disease, first SCT) and 20% (second or third SCT, any disease status). This approach allows first or subsequent haploidentical SCTs to be performed with low TRM. Patients in CR may benefit from SCT, whereas the results in patients with active disease were poor.